Neuroticism, depression and anxiety in takotsubo cardiomyopathy. Issue 1 (December 2016) - Christensen, Thomas; Bang, Lia; Holmvang, Lene; Hasbak, Philip; Kjær, Andreas; Bech, Per; Østergaard, Søren
Abstract Background Takotsubo cardiomypathy (TTC) causes acute reversible heart failure. Prior studies have indicated that the syndrome is associated with traits such as social inhibition, chronic psychological stress, and anxio-depressive disorders. The objective of this study was to further characterize key psychological/psychopathological traits of patients with TTC. Methods A survey of three groups was conducted: I) Female post-recovery TTC patients admitted between October 1st 2009 and December 10th 2014, II) Age, gender and geographically matched ST-elevation myocardial infarction (STEMI) patients, and III) Age, gender and geographically matched individuals from the background population. The following questionnaires were used in the survey: the WHO-5 Well-Being Index, Eysenck's Neuroticism Scale, the Major Depression Inventory, and the anxiety subscale of Symptoms Checklist (SCL-90). Results In total, 173 of 230 invitees (75 %) participated in the study. In comparison to the background controls, TTC patients reported significantly less well-being, more neuroticism, more depression, and more anxiety. The levels of well-being, depression and neuroticism were comparable between TTC and STEMI patients, but the level of anxiety was higher in the TTC patients. There was a negative correlation between the time since TTC admission and the total scores on the psychopathology rating scales. Conclusions Patients with TTC reported significantly higher anxiety levels compared to both STEMI patients and background controls. However, unlike the STEMI patients, the TTC patients appeared to improve psychologically during the post-recovery phase. This may be a consolation for TTC patients in acute psychological distress.